UNCOVERING IMPLIED MESSAGES IN BURGER KING ADVERTISEMENT: A SEMIOTIC ANALYSIS - Ida Bagus Putra Wirasana (Lingua Scientia, 2021)
This article is entitled “Uncover Implied Messages in Burger King Advertisement Found on Youtube: A Semiotic Analysis”. Burger King is one of the multinational chain used video as their advertisement related to COVID-19 pandemic that uses weird and eccentric verbal and visual signs, which not easy to understand and carried implied messages. This study aims to find out the implied messages in Burger King Advertisement found on YouTube by analyzing its verbal and visual signs. The data was taken from Burger King YouTube channel using observation method. Furthermore, it analyzed descriptive qualitative method using theory of semiotics by Saussure (1983) and Barthes (1998). The finding shows that both verbal and visual signs in the advertisement “Burger King | Stay Home of the Whopper” had hidden messages. Generally, they want to help the government stop the spread of COVID-19 virus by informing and educating their viewers about current procedures and situations.